Translocating kilobase RNA through the Staphylococcal α-hemolysin nanopore. - Cracknell, J; Japrung, D; Bayley, H (2013)
The electrophoretic translocation of polynucleotides through nanopores may permit direct single-molecule nucleic acid sequencing. Here we describe the translocation of ssRNA heteropolymers (91-6083 bases) through the α-hemolysin nanopore. Translocation of these long ssRNAs is characterized by surprisingly long, almost complete ionic current blockades with durations averaging milliseconds per base (at +180 mV). The event durations decrease exponentially with increased transmembrane potential but are largely unaffected by the presence of urea. When the ssRNA is coupled at the 3' end to streptavidin, which cannot translocate through the pore, permanent blockades are observed, supporting our conclusion that the transient blockades arise from ssRNA translocation.